La Oscurana (Cajamarca), one more relict forest to be conserved from the western Andean slopes in northern Peru - Juárez, Ana M. (2005)
Floristic composition, the life forms, the importance and strategies for the conservation of a newly discovered relict forest in the north of Peru, called La Oscurana, are analyzed (El Nogal Hamlet, Bolívar District, San Miguel de Pallaques Province, Cajamarca Department; 6° 90’ S y 79° 08’ W, 2000- 2800 m). The preliminary analysis includes 85 families, 169 genera and 258 species of vascular plants, 15 families are Pteridophyta and 70 Magnoliophyta. The family with the most genera and species are the Asteraceae in the Magnoliopsida, and the Orchidaceae in the Liliopsida. The predominant life forms of the families can be divided in 6 different categories: herbs 29 (34%), shrubs 14 (16%), trees 9 (11%), lianas 9 (11%), herbs/shrubs 7 (8%) and epiphytes 5 (6%). The exceptional diversity and the local economic use are discussed. The conservation of this fragile and important ecosystem is urgent. It is one of the last existing relict forests in the region. The forest should be declared as a protected zone. Scientists, state officials, members of the regional government and the local people should work out together in the conservation plan.